Polypoidal Choroidal Vasculopathy Complicating Retinal Laser in Quiescent Uveitis - Tomas R. Burke; Susan L. Lightman (Case Reports in Ophthalmological Medicine)
A 58-year-old Afro-Caribbean gentleman with a diagnosis of quiescent systemic lupus erythematosus- (SLE-) related occlusive retinal vasculitis was previously treated with sector pan-retinal photocoagulation in his right eye to control temporal retinal neovascularization. At routine review he was found to have a focal area of subretinal fluid in the temporal macula sparing an ischaemic fovea. Fundus fluorescein angiography and indocyanine green angiography confirmed a branching vascular network (BVN) and terminal polys (i.e., polypoidal choroidal vasculopathy (PCV)). Interestingly, the BVN arose within an old laser scar. To our knowledge this is the first report of PCV in uveitis in an Afro-Caribbean patient and of the lesions arising within a laser scar.